Chemotherapy-Related Encephalopathy With Super-Refractory Status Epilepticus in a Child With Osteosarcoma: A Case Report With a Review of Literature - Di Genova, Lorenza; Perruccio, Katia; Celani, Maria Grazia; Mastrodicasa, Elena; Cantisani, Teresa Anna; Esposito, Susanna; Caniglia, Maurizio (Frontiers in Pharmacology, 2019)
Osteosarcoma is the most frequent primary cancer of the bones and a combination of primary chemotherapy, surgery and adjuvant chemotherapy is its current treatment. in adults, some authors have reported problems with memory and concentration following chemotherapy, but in children severe neurologic dysfunction have been rarely reported. This report describes a 13-year-old patient with primary high-grade nonmetastatic osteosarcoma of the tibia who developed encephalopathy with super-refractory status epilepticus related to chemotherapy. He received methotrexate (MTX) and cisplatin (CDDP)-containing polychemotherapy and after the first course of drug administration he developed fever, confusion, a state of psychomotor agitation and super-refractory status epilepticus with normal laboratory and imaging findings. The causal relationship between the administration of the first polychemotherapy course and his neurological manifestations may be supported by the evaluation and exclusion of other causes. The administration of antiepileptic drugs and off-label atypical antipsychotics was necessary to treat his neurological complications and behavioural changes. This patient represents the first known example of super-refractory status epilepticus (SE) in a child treated with MTX and CDDP-containing chemotherapy. Physicians should be aware that encephalopathy and seizures are possible consequences of CDDP therapy when administered alone or in combination with other chemotherapeutic agents. Further studies are needed to better define this relationship in children.